Digging Deeper Into the Pyriproxyfen-Response of the Amphipod Gammarus fossarum With a Next-Generation Ultra-High-Field Orbitrap Analyser: New Perspectives for Environmental Toxicoproteomics - Trapp, Judith; Gouveia, Duarte; Almunia, Christine; Pible, Olivier; Degli Esposti, Davide; Gaillard, Jean-Charles; Chaumot, Arnaud; Geffard, Olivier; Armengaud, Jean (Frontiers in Environmental Science, 2018)
Taxon-specific proteins from sentinel species have been shown to be among the most relevant proteins to monitor the biological effects of anthropogenic contaminations. Shotgun proteomics allows high-throughput analysis of animal proteomes, but comprehensive coverage remains difficult to achieve due to the wide dynamic range. Here, the advantages of a new generation of mass analyser for environmental toxicoproteomics are documented through the identification of candidate biomarkers in a sentinel animal species for which the genome is as yet unsequenced. A label-free comparative proteomic study was performed on testis from the freshwater amphipod Gammarus fossarum challenged with 0.5 µg or 50 µg/L pyriproxyfen, a juvenile hormone analogue used as an insecticide. A total of 4,031 proteins could be monitored with a Q Exactive HF mass spectrometer incorporating an ultra-high-field Orbitrap analyser. Five times more MS/MS spectra and 4-fold more peptides and proteins were identified with this instrument compared to a LTQ Orbitrap XL spectrometer. Comparison of protein abundance between control and organisms exposed to 0.5 µg or 50 µg/L pyriproxyfen indicated that 32 and 21 proteins, respectively, were significantly modulated between test and control conditions. Functional annotation of these novel candidate biomarkers and their specificities are discussed in light of their potential applications in freshwater quality monitoring. The potential contribution of next-generation mass spectrometers to environmental toxicoproteomics is also touched on.